2019
DOI: 10.1186/s12866-019-1663-8
|View full text |Cite
|
Sign up to set email alerts
|

Thymol tolerance in Escherichia coli induces morphological, metabolic and genetic changes

Abstract: BackgroundThymol is a phenolic compound used for its wide spectrum antimicrobial activity. There is a limited understanding of the antimicrobial mechanisms underlying thymol activity. To investigate this, E. coli strain JM109 was exposed to thymol at sub-lethal concentrations and after 16 rounds of exposure, isolates with a 2-fold increased minimal inhibitory concentration (MIC) were recovered (JM109-Thyr). The phenotype was stable after multiple sub-cultures without thymol.ResultsCell morphology studies by sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…Thy and bioAgNP alone significantly caused ROS production in E. coli compared to the untreated control, in line with other studies (Kim et al, 2011;Li et al, 2014;Ninganagouda et al, 2014;Shen et al, 2016;Yan et al, 2018;Al-Kandari et al, 2019); the combination of Thy and bioAgNP also increased ROS production by E. coli. In addition to protein oxidation, lipid oxidation also occurred.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thy and bioAgNP alone significantly caused ROS production in E. coli compared to the untreated control, in line with other studies (Kim et al, 2011;Li et al, 2014;Ninganagouda et al, 2014;Shen et al, 2016;Yan et al, 2018;Al-Kandari et al, 2019); the combination of Thy and bioAgNP also increased ROS production by E. coli. In addition to protein oxidation, lipid oxidation also occurred.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, exactly at the beginning of treatment with Thy (0 h), E. coli produced significantly higher amount of ROS than the untreated control (Figure 3A). Although the antioxidant activity of Thy has been reported on animal cells (Chauhan and Kang, 2014;Coccimiglio et al, 2016;Nagoor Meeran et al, 2017), some studies have shown that its antimicrobial activity involves ROS production (Shen et al, 2016;Al-Kandari et al, 2019). Yuan et al (2018) showed that genes related to oxidative stress defense were upregulated in Thy-treated E. coli O157:H7.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Wu et al (2008) showed that andrographolide alone or combined with standard drugs induced no change in gene expression. The mechanism of action of the monoterpene thymol ( Al-Kandari et al, 2019 ) was associated with the alteration of the membrane permeability and induction of genetic and morphological changes that lead to inhibition of the expression of AcrAB-TolC efflux pump in Escherichia coli. Accordingly, Lorenzi et al (2009) showed that the terpene geraniol inhibited chloramphenicol’s efflux, which was mediated by the AcrAB-TolC system.…”
Section: Resultsmentioning
confidence: 99%
“…It is demonstrated that thymol exerts its antimicrobial power by permeabilizing and depolarizing bacterial membranes thanks to its pore-forming activity [ 18 , 43 ]. Despite the similarity of its mechanism of action with several antibiotics, resistance determinants do not currently seem to affect thymol or other nature-identical compounds [ 44 ]. For this reason, the aim of this study was to investigate if thymol, as a representative of nature-identical compounds, could re-establish the efficacy of conventional antibiotics by exerting an adjuvant effect.…”
Section: Discussionmentioning
confidence: 99%